Multiprofessional approach to the promotion and prevention of pressure injuries in bedridden patients in a hospital in Belém do Pará: na experience report (Research, Society and Development, 2021)
Pressure injury (LPP) is caused by a blood interruption in a certain area of the body, which develops due to pressure for a long period of bed in Intensive Care Unit (ICU) beds. PPL, unlike other skin changes, has been a source of concern for representing a public health problem, leading to physical and emotional disorders and influencing morbidity and mortality. This is a descriptive study, of the experience report type, carried out in an infirmary of a reference hospital in Belém, Pará, during supervised internship practices. Patients who need to go to the ICU, and who are bedridden for undetermined reasons, end up developing PPL, due to humidity, friction, among other factors. Nursing care with the multidisciplinary team is crucial for the evolution of improvement in the lesion, without causing harm to the patient, in addition to providing the best treatment adherence. Therefore, there is a need to pass on to professionals what was observed, so that they provide multidisciplinary care in a clear way, so that no complications that may be caused by LPP occur.